مؤشر هیرش( H index ) وتعدیلاته المختلفة کأداة لتقییم الباحثین :دراسة نظریة - د.نورا أحمد عبد الحمید زاید (المجلة الدولية لعلوم المكتبات والمعلومات)
The h index Is a bibliometric indicator that evaluates an author-levelmetric and attempts to measure both the productivity and citation impact of thepublications of a scientist or scholar. The index is based on the set of thescientist's most cited papers and the number of citations received in otherpublications. The index can also be applied to the productivity and impact of anacademic journal as well as a group of scientists, such as a department oruniversity or country.[2] The index was suggested in 2005 by Jorge E. Hirsch, aphysicist at UC San Diego, as a tool for determining theoretical physicists'relative quality[3] and it is sometimes called the Hirsch index or Hirsch numberTherefore, this study aims to identify this index and to determine the mostimportant advantages, disadvantages, and the most important revisions